Numerical Simulation of Metal Forming Processes for the Production of Microparts - Engel, Ulf; Messner, A. (Wire, 1998)
The application of the metal forming technology for the production of microparts is still characterized by an empirical process design. To improve this situation the numerical process simulation seems to be a suitable instrument. A simply applicable concept for a size dependent description of the flow stress is proposed which requires the experimental determination of the flow stresses of two different specimen dimensions. The application of this concept for the numerical simulation of the flat upsetting process of smallest cylindrical billets yields a force-displacement curve excellently coinciding with the experimental results.
LFT Import::2019-07-16 (1373)